When the Sacred Meets the Market: The Commodification of Islamic Housing in Lima Puluh Kota, West Sumatra - Putra, Muhammad Deni; Rofiki, Akhmad; Yudha, Ana Toni Roby Candra; Riyadi, Ivan; Fadilla, Siti (Journal of Islamic Law, 2025)
This study examines the commodification of religion and structural tensions in Islamic housing finance in Lima Puluh Kota, West Sumatra, Indonesia. Despite its rapid growth, Islamic housing frequently encounters a paradox between religious claims and market logic, where Islamic symbols are leveraged as marketing strategies rather than ensuring substantive justice. This article analyzes the factors driving middle-class Muslim preferences for Islamic housing and the power imbalances between developers and consumers in Sharīʿah-compliant transactions. Employing a socio-legal qualitative approach, the research draws on in-depth interviews with 10 stakeholders (developers and buyers) and an analysis of contractual documents and promotional materials from the Perumahan Syariah Residence. Three primary motivations for purchasing emerge: religious adherence (particularly usuryavoidance), economic considerations (flexible payment schemes), and the preference for religiously homogeneous communities. However, the findings reveal critical tensions: while istisnāʿ (manufacture-sale) contracts disproportionately burden developers with financial risks, ijārah muntahiyah bi tamlīk (lease-to-own) arrangements often marginalize consumers’ legal standing. The Islamic label frequently functions as a branding tool rather than a guarantee of justice, reinforcing spatial segregation among middle-class Muslims. This study argues that without business model reformulation and regulatory oversight, Islamic housing risks prioritizing commercial interests over the principles of maqāṣid al-sharīʿah (the objectives of Islamic law). The findings underscore the necessity of standardized contracts and risk mitigation mechanisms to align practice with Islamic values. [Artikel ini mengkaji fenomena komodifikasi agama dan ketegangan struktural dalam pembiayaan perumahan syariah di Lima Puluh Kota, Sumatera Barat, Indonesia. Meskipun mengalami pertumbuhan pesat, praktik perumahan syariah kerap terjebak dalam paradoks antara klaim religiositas dan logika pasar, di mana simbol-simbol Islam dimanfaatkan sebagai strategi pemasaran tanpa disertai dengan implementasi keadilan substantif. Studi ini bertujuan untuk menganalisis faktor-faktor yang mendorong preferensi kelas menengah Muslim terhadap perumahan syariah serta ketimpangan relasi kuasa antara pengembang dan konsumen dalam transaksi berbasis syariah. Penelitian ini menggunakan pendekatan kualitatif sosio-legal dengan mengumpulkan data primer melalui wawancara mendalam terhadap 10 informan (pengembang dan pembeli), serta analisis dokumen kontrak dan materi promosi dari Perumahan Syariah Residence di Sumatera Barat. Hasil penelitian mengungkap tiga motif utama pembelian: kepatuhan religius (khususnya penghindaran riba), pertimbangan ekonomi (skema pembayaran yang fleksibel), dan preferensi terhadap lingkungan yang homogen secara agama. Namun, akad syariah yang digunakan dalam transaksi perumahan ini justru menciptakan risiko yang tidak seimbang. Akad istisnāʿ membebani pengembang dengan risiko finansial yang tinggi, sementara akad ijārah muntahiyah bi tamlīk berpotensi meminggirkan posisi hukum konsumen sepanjang masa sewa. Selain itu, label syariah dalam industri ini sering kali berfungsi sebagai alat pemasaran daripada sebagai jaminan keadilan substantif, yang pada akhirnya memperkuat segregasi spasial dalam komunitas Muslim kelas menengah. Studi ini berargumen bahwa tanpa reformulasi model bisnis dan pengawasan regulasi yang lebih ketat, perumahan syariah berisiko mengorbankan prinsip maqāṣid al-sharīʿah demi kepentingan komersial. Oleh karena itu, diperlukan standarisasi kontrak dan mekanisme mitigasi risiko yang lebih efektif guna memastikan keselarasan antara praktik perumahan syariah dengan nilai-nilai Islam.]